2020
DOI: 10.1161/circulationaha.119.044366
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Cardiomyopathy With Left Ventricular Systolic Dysfunction

Abstract: Background: The term “end stage” has been used to describe hypertrophic cardiomyopathy (HCM) with left ventricular systolic dysfunction (LVSD), defined as occurring when left ventricular ejection fraction is <50%. The prognosis of HCM-LVSD has reportedly been poor, but because of its relative rarity, the natural history remains incompletely characterized. Methods: Data from 11 high-volume HCM specialty centers making up the international SHaRe Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
117
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(134 citation statements)
references
References 23 publications
(33 reference statements)
4
117
0
1
Order By: Relevance
“…Many diagnoses of obstructive hypertrophic cardiomyopathy are amenable to surgical debulking and ablative therapies with excellent results, and do not result in death, transplantation, or cardiac assist device implantation. In a review of 6793 patients with hypertrophic cardiomyopathy, 553 (8.1%) patients exhibited left ventricular systolic dysfunction with an even smaller subset of these patients requiring OHT 11 . Regardless, this predilection towards younger presentation and lack of other associated comorbidities may explain the greatest age‐adjusted odds of long‐term survival found in this population after OHT.…”
Section: Discussionmentioning
confidence: 99%
“…Many diagnoses of obstructive hypertrophic cardiomyopathy are amenable to surgical debulking and ablative therapies with excellent results, and do not result in death, transplantation, or cardiac assist device implantation. In a review of 6793 patients with hypertrophic cardiomyopathy, 553 (8.1%) patients exhibited left ventricular systolic dysfunction with an even smaller subset of these patients requiring OHT 11 . Regardless, this predilection towards younger presentation and lack of other associated comorbidities may explain the greatest age‐adjusted odds of long‐term survival found in this population after OHT.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-differences in clinical presentation contribute to the phenotypic heterogeneity of HCM. Several large cohort studies observed a higher disease prevalence in men representing 55-65% of the total HCM population (7)(8)(9)(10)(11). At HCM diagnosis, women are on average 9 years older than men (7,12), and at the time of myectomy surgery women are on average 7 years older than men (13).…”
Section: Introductionmentioning
confidence: 99%
“…The yield of clinical screening is higher in families where the disease onset has been in childhood (9,10). HCM featuring the so-called dilated-hypokinetic or 'burnt-out' phase (5), or due to specific gene mutations (11)(12)(13), can be associated with only mild increases in wall thickness. Grey Cases Ethnicity, hypertension, renal disease, significant aortic stenosis, increased body mass index and athletic remodelling all influence left ventricular hypertrophy.…”
mentioning
confidence: 99%
“…To allow this critical information to be accessed rapidly by the referring clinician, the conclusion for every report in a patient with suspected or confirmed HCM should contain these parameters. Although not in the ESC risk calculator, the presence of left ventricular impairment (5) and an apical aneurysm(25) is also essential to include in the study conclusion as they modify risk of sudden cardiac death. The importance of reporting cardiac rhythm in every echocardiogram report is particularly relevant in HCM as a significant proportion of patients will develop atrial fibrillation.…”
mentioning
confidence: 99%
See 1 more Smart Citation